Determinant factors in increasing the livability of the city of Padang from the perspective of transportation - Yosritzal Yosritzal; Rizki Aziz; Melinda Noer; Dita Oktaviani Putri; Abdullah Sani (Universitas Mercu Buana, 2023)
Padang has been determined to be a livable city in 2024, according to the Mission of the City Major 2019-2024. Some improvements have been made, such as more BRT corridors, widening the sidewalk, and adding benches along the sidewalks. However, achieving a livable city is far more than just those thingies; we also need to know what people need and what the government is willing to do. This study explores the determinant factors in achieving the livable city criterion for Padang, especially regarding transportation-related variables in the expert views along and public and government interests. The quadrant analysis of Expectation-Performance and Effort-Effect Analysis was used to identify the determinant and priority factors in improving the livability of Padang. The results show that improving some essential elements has satisfied public expectations. Still, more things need to do, such as an integrated transportation system, comfortable public transportation, transportation for disabled persons, and a more environmentally friendly transportation mode. With less effort and high effect, the most priority factors are comfortable and secure pedestrian facilities, improving traffic to reduce travel time, and improving public transport facilities.